LEARNING MIRROR READING USING THINK PAIR AND SHARE METHOD IN CLASS X SMA STUDENTS - Firman Safaat (IKIP Siliwangi, 2021)
Learning to read short stories using the Think, Pair, and Share methods is learning to read a short story text through the steps of learning to think, pair up, and share with class X students of Albidayah High School Academic. This study aims to determine whether there are differences in student learning outcomes by using the Think, Pair, and Share Methods in the short story reading subjects. The research method used is Quasi Experimental Design which is a development of True Experimental Design. The form of research chosen was the type of Nonequivalent Control Group Design. The population in this study were all class X students of Albidayah High School with a sample of two classes totaling 60 students. The research data were obtained using the instrument in the form of a description test given at the time of the initial test before learning began and the final test after conducting the learning process with the same type of questions. The results obtained an average of 80.6 experimental class while in the control class obtained an average of 72.8 in the final test. Based on the initial T-test calculation results obtained 0.232 while the Mann-Whitnay calculation obtained 003 results. The results of this study indicate that learning to read short stories using the Think, Pair, and Share methods is effectively applied to learning to read short stories. 6 experimental class while in the control class obtained an average of 72.8 in the final test. Based on the initial T-test calculation results obtained 0.232 while the Mann-Whitnay calculation obtained 003 results. The results of this study indicate that learning to read short stories using the Think, Pair, and Share methods is effectively applied to learning to read short stories. 6 experimental class while in the control class obtained an average of 72.8 in the final test. Based on the initial T-test calculation results obtained 0.232 while the Mann-Whitnay calculation obtained 003 results. The results of this study indicate that learning to read short stories using the Think, Pair, and Share methods is effectively applied to learning to read short stories.